2020
DOI: 10.1371/journal.pone.0230427
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 contributes to PGE2 signalling through upregulation of EP4 via SHIP1 and STAT3

Abstract: Macrophage cells form part of our first line defense against pathogens. Macrophages become activated by microbial products such as lipopolysaccharide (LPS) to produce inflammatory mediators, such as TNFα and other cytokines, which orchestrate the host defense against the pathogen. Once the pathogen has been eradicated, the activated macrophage must be appropriately deactivated or inflammatory diseases result. Interleukin-10 (IL10) is a key anti-inflammatory cytokine which deactivates the activated macrophage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…Autocrine/paracrine produced prostaglandin E2 (PGE2) binds to the prostaglandin E2 receptor 4 (EP4) and can support proliferation of PCa cells by stimulating PI3K/Akt and cAMP-dependent PKA pathways [ 42 ]. PGE2 has been reported to induce NED phenotype in PCa cells [ 43 ], and in our work with macrophages we found that IL10 induction of EP4 protein is required for IL10 action in these cells [ 44 ]. Thus, we examined whether IL10 or IL6 might upregulate EP4 expression to promote PGE2-induced NED.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Autocrine/paracrine produced prostaglandin E2 (PGE2) binds to the prostaglandin E2 receptor 4 (EP4) and can support proliferation of PCa cells by stimulating PI3K/Akt and cAMP-dependent PKA pathways [ 42 ]. PGE2 has been reported to induce NED phenotype in PCa cells [ 43 ], and in our work with macrophages we found that IL10 induction of EP4 protein is required for IL10 action in these cells [ 44 ]. Thus, we examined whether IL10 or IL6 might upregulate EP4 expression to promote PGE2-induced NED.…”
Section: Resultsmentioning
confidence: 78%
“…We also examined whether IL10 or IL6 might upregulate the PGE2 receptor, EP4, to promote PGE2-induced NED. In our studies of IL10 action in macrophage cells, we found IL10 induction of EP4 protein expression is needed for IL10 inhibition of macrophage production of inflammatory cytokines [44]. In PCa cells, activation of EP4 by PGE2 has been reported to increase the expression of metastatic-related proteins [42].…”
Section: Cell Line Nse Expression Syp Expressionmentioning
confidence: 75%
“…Recent evidence suggests the existence of a regulatory interplay between the production of certain cytokines or chemokines and the synthesis/action of eicosanoids or their receptors. This is exemplified by studies showing that TNFα and PGE 2 act synergistically to induce IL-8 expression [ 61 ], and that IL-10, a cytokine with proven anti-inflammatory functions, contributes to PGE 2 signaling through the upregulation of the EP4 receptor [ 62 ]. Therefore it seemed reasonable to investigate whether a connection existed in our system between early PG production and cytokine expression.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that a protein other than STAT3 might contribute to IL10 action. Our previous cell-culture-based studies suggested that SHIP1 participates in IL10 action ( Chan et al., 2012 ; Cheung et al., 2013 ; Samiea et al., 2020 ). We now looked in vivo at the ability of IL10 to inhibit LPS-induced inflammatory cytokine expression ( Figure 1 A) in SHIP1 +/+ and SHIP1 −/− mice and found IL10 inhibited TNFα in SHIP1 +/+ but not SHIP1 −/− mice.…”
Section: Resultsmentioning
confidence: 99%